Karier atau Peran Mengasuh: Dilema yang Dihadapi oleh Perempuan dalam Generasi Sandwich - Moh. Khusaini; Firdaus Finuliyah; Alfi Muflikhah Lestari; Alma Sofi Yuwan (Society, 2024)
This study analyses the factors of working women in a sandwich generation to decide to work in the non-agricultural sector in East Java Province, Indonesia. The sandwich generation is identical to economic dependents on two families simultaneously: biological children and parents. As a sandwich generation, encouraging women to work develops their careers and for the welfare of their families. The sandwich generation phenomenon has occurred in several countries, including in every region in Indonesia. Many factors, especially structural poverty and economic conditions, can cause sandwich generation. This study uses logistic regression analysis of 2022 National Socioeconomic Data. The research results show that the characteristics of women participating in the non-agricultural sector can be caused by living conditions, education level, digital conditions, and the guarantee of protection from the government.